CYP17 inhibitors in prostate cancer: latest evidence and clinical potential. (July 2016) - Alex, Anitha B.; Pal, Sumanta K.; Agarwal, Neeraj
Since androgen signaling plays a pivotal role in the proliferation and metastasis of prostate cancer, androgen deprivation therapy (ADT) or castration therapy is considered the backbone of treatment for newly diagnosed metastatic prostate cancer. However, almost all men experience disease progression on ADT to a state known as metastatic castration-resistant prostate cancer (mCRPC), which continues to be driven by intratumoral androgen synthesis or androgen receptor signaling. Hence, the extragonadal ablation of androgen synthesis from pregnane precursors holds much promise. An inhibitor of cytochrome P450 17α−hydroxy/17, 20-lyase (CYP17) enzymes, abiraterone acetate, has already been approved for men with mCRPC. Newer CYP17 inhibitors continue to be developed which are either more selective or have concomitant inhibitory actions on AR signaling. These include VT-464, orteronel, and galeterone. Herein, we focus on the molecular mechanism of action, efficacy, latest evidence, and clinical potential of CYP17 inhibitors in prostate cancer.